Why the Kemeny Time is Constant - (:unkn) unknown (Cornell University Library, 2015)
We present a new fundamental intuition for why the Kemeny feature of a Markov chain is a constant. This new perspective has interesting further implications.
Keywords: Markov chains; Mixing; Kemeny constant